Productive Organisational Energy and Performance in Estonian Football Organisations - Aidla Anne; Iliushchenkov Georgii (Sciendo, 2023)
Sports governance is a broad domain in which many ambitious goals are expected to be considered by top management. Attending to productive organisational energy may be the key to consolidating and amplifying efforts by members of sports organisations at individual, group and organisational levels in order to achieve those wide-ranging goals. The aim of the article is to discover whether Estonian football organisations with higher results for the dimensions of productive organisational energy also show higher performance. Overall, we reached about 14% of the population of players, coaching staff and management from football organisations in Estonia. Productive organisational energy was measured using affective, cognitive and behavioural dimensions (Cole et al., 2012). Rankings in the league tables for 2020, 2021 and 2022 reflected the performance of the football clubs. The results demonstrated that football clubs that had higher levels of productive organisational energy were mostly placed in the top half of the league table. All three dimensions of productive organisational energy were similarly relevant in regard to performance. The connection between productive organisational energy and performance has so far been analysed only in business organisations and in one health service organisation. We brought the topic to the sports context and distinguished three dimensions of productive organisational energy while comparing the performance of organisations, which has not been done before. We also conducted the first empirical study that considers whether dimensions of productive organisational energy are balanced in better performing clubs.